The Influence of Work Motivation and Self-Actualization on Work Productivity of Nursing Staff Nursing Staff in The Surgical Clinic of The Hospital TK II Iskandar Muda Hospital Banda Aceh - Sandha Medika Permana; Deden Komar Priatna; Widiya Avianti (Greenation Publisher & Yayasan Global Research National, 2023)
The purpose of this research is to know and analyze: (1) motivation; (2) Actualization; (3) Productivity; and (4) The Effect of Work Motivation and SelfActualization on the Work Productivity of Nurses at the Surgical Clinic of the Iskandar Muda Level II Hospital, either simultaneously or partially. The research method used in this study was a descriptive survey and an explanatory survey. The analysis used in this study was the nurses at the Surgical Clinic, Iskandar Muda Level II Hospital, with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Productivity of Nurses at the Surgical Clinic at TK II Iskandar Muda Hospital in Banda Aceh turned out that most of the Nurses gave very good responses; The work productivity of nurses at the Surgical Clinic of the Iskandar Muda Level II Hospital in general can be said to be good, the Work Productivity of Nurses at the Surgical Clinic of the Iskandar Muda Banda Aceh Kindergarten Hospital is currently considered good from the research results of data processing and analysis of 0.894. Work Motivation and SelfActualization simultaneously affect the Work Productivity of Nurses at the Surgical Clinic, Iskandar Muda Banda Aceh Level II Hospital. But partially Work Motivation of 0.673 more dominantly affects the work productivity of nurses than selfactualization of 0.360. Thus, Work Motivation is more dominant in influencing Work Productivity, being the first priority in improving Nurse performance. then the Surgical Room of the Iskandar Muda Banda Level II Hospital is expected from the leadership to continue to be able to provide Work Motivation to the Nurses on a regular basis so that providing services at the Surgery Clinic runs optimally while the nurse staff is included in training and education, so that they can work well and get patient or community trust.